Mandibular defect rehabilitation with conventional removable partial denture: Case report - Phonepaseuth Sitthiphan (2018)
Background: The ameloblastoma is a bening odontogenic tumor. The treatment planning in young person's is still not clear as well as the recurrence rate of amloblastoma, and the reconstruction of mandibular defects following tumor resection with bone graft is considered to be a treatment option, and different donor sites, such as the iliac crest, the fibula, the scapula, and the radius, have been recommended recently. Each bone graft has its specific advantages and disadvantages. Case presentation: A 27-year-old Thai female patient was diagnosed with ameloblastoma on left posterior aspect of the mandible. Following which the patient underwent segmental mandibulectomy, reconstruction of the mandible was done with iliac crest bone graft. No deviation of the mandible was observed following the reconstruction. Results: The rehabilitation of the patient was carried out with removable partial denture prostheses which replaced the missing dentition on the defect side. Conclusion: The patient reported satisfactory function following the rehabilitation and was followed up for 6 months without any recurrence of the tumor. © 2013 Japan International Cultural Exchange Foundation and Japan Health Sciences University.